Formalising 'informal' mHealth in Ghana: Opportunities and challenges for Universal Health Coverage (UHC). Issue 5 (4th May 2022) - Mariwah, Simon; Machistey Abane, Albert; Asiedu Owusu, Samuel; Kasim, Adetayo; Robson, Elsbeth; Castelli, Michele; Hampshire, Kate
ABSTRACT: While mobile phones promise to be an important tool for bridging the healthcare gaps in resource-poor areas in developing countries, scalability and sustainability of mobile phones for health (mhealth) interventions still remain a major challenge. Meanwhile, health workers are already using their own mobile phones (referred to as 'informal mhealth') to facilitate healthcare delivery in diverse ways. Therefore, this paper explores some strategies for integrating 'informal mHealth' in the healthcare delivery of Ghana, by highlighting some opportunities and challenges. The study mainly employed a combination of literature review, focus group discussions and key informant interviews with community health nurses (CHNs) and other stakeholders, who were purposively selected from the three ecological zones in Ghana. The study found that, while scale-up of 'formal mhealth' remains challenging in Ghana, almost all CHNs in our study are using their personal mobile phones 'informally' to bridge healthcare gaps, thereby promoting universal health coverage. This provides opportunities for promoting (or formalising) 'informal' mhealth in Ghana, in spite of some practical challenges in the use of personal mobile phones that need to be addressed to ensure sustainable healthcare delivery in the country.